Penetapan Kadar Kofein Daun Kopi Kawa ( Coffea Robusta ,Lind ) - Roslinda Rasyid; Winaldi Fitra Sanjaya; Zulharmita Zulharmita (Jurnal Farmasi Higea, 2013)
Research has been done on the determination of caffeine that leaves Kawa Coffee  ( Coffea robusta Linden ex DE Wildem ) by using  Soxlhetation method. Coffein from extraction purified by preparative TLC mobile phase solution  chloroform : methanol ( 9:1 ).The constration of pure Coffein from preparative TLC has been determinedby using Spectrophotometer Uv-Vis T -70 .The result Coffea Kawa leaves (Coffea robusta Limden ex De Wildem )   is 0.7 % w/w